PENGARUH PENGETAHUAN PERJAKAN DAN SOSIALISASI PAJAK TERHADAP MOTIVASI WAJIB PAJAK UMKM DI KOTA SOLOK - Putri, Hemalia; Das, Nidia Anggreni; Wahyuni, Lili (Universitas Bina Bangsa, 2024)
This study aims to determine the Influence of Tax Knowledge (X1) and Tax Socialization (X2) on the Motivation of MSME Taxpayers (Y) in Solok City. This research was conducted on MSME taxpayers in Solok City in 2023. In this study, data collection techniques were used by distributing questionnaires (questionnaires). The data analysis techniques used were descriptive statistics, normality, multicollinearity, heteroscedacity, double linear analysis, determination coefficient, partial test, and simultaneous test. The results of the study show that the influence of tax knowledge has a positive and significant effect on taxpayer motivation. Tax socialization has a positive and significant influence on taxpayer motivation. Therefore, it can be concluded that tax knowledge is accepted, and tax socialization is accepted